Uma comparação dos tipos de enunciados de problemas matemáticos na abordagem de equação do 1° grau nos livros didáticos Matemática Bianchini e Compreensão e Prática (PNLD 2017 e 2020) - Souza, Barbara Bettina Oliveira (2024)
In the present work presents the result of research that aims to compare types of statements of mathematical problems in the approach to Equação do 1° Grau in the textbooks Mathematics Bianchini and Comprehension and Practice (PNLD 2017 and 2020). It is worth highlighting that the fonts selected by them will be examples of the collection most suitable for use in public schools of Aracaju/SE, from PNLD 2017, as they will be among the three works two Years Finals most selected by PNLD 2020. A northern investigation that unleashed a The research was as follows: What are the types of mathematical problem statements identified in the teaching books of Mathematics in editions different from PNLD, about the 1st Grade Equation? To respond to this inquiry, two movements were made, first of all, there was a map of the dissertations related to thematic topics available in BDTD, in which were selected the dissertations of Trindade (2012) and Corá (2019) for a bibliographic review. From the appropriation of the understanding of mathematical problems, given to the authors of these dissertations, prioritizing the work of two statements from the classification established by Dante (2005). In a second move, it was initially carried out to typify two statements present in the approach to the equation of the 1st grade of the selected exemplars from different PNLD to then carry out a comparison. As a result of typifying our exemplars from the Bianchini Mathematical School, we identified one hundred and seventy-one problems, and in our exemplars of Mathematics Comprehension and Practice, we identified two and three problems. Thus, to compare them, it was possible to identify that in both the exemplars, except the work of Silveira (2015), no problem was found - process or heuristic, were identified algorithm exercise, recognition exercise, simple and composite master problem, problem – process or heuristic, application problem and brain-brain problems, being the most identified, in all the examples, the main problem.